Mechanical Property Performance of Fe-SnS Hybrid Reinforced Aluminum Composites - Kolawole, Maruf Yinka; Bello, Sefiu Adekunle; Babatunde, Tolulope Peace; Adebayo, Kehinde Raheef (Kathmandu University Journal of Science, Engineering and Technology, 2023)
In this paper, the mechanical properties of a hybrid iron filing (Fe)-snail shell (SnS)-reinforced discarded aluminum matrix were investigated. Prepared iron filling (20 µm) and snail shell (70 µm) particulates at a mix ratio of 1:3 constituting 2, 4, 6, and 8 wt% in hybrid weight fractions as the reinforcing phase in the aluminum matrix were investigated. Both the unreinforced aluminum matrix and the reinforced hybrid composites were produced via a double-stir die casting technique. Metallurgical optical examination, density, tensile, hardness, and impact testing were carried out to appraise the mechanical property performance of the developed composites relative to the unreinforced Al matrix. The results show that with increasing hybrid-Fe-SnS particulates in the reinforcing phase, the hardness and ultimate tensile strength (UTS) of the reinforced Al-matrix composite also increase. The maximum tensile strength (106.10 MPa) and hardness value (62.92 HRB) equivalent to 86.50% and 24.90% increments, respectively, were obtained at 8 w% of the hybrid reinforcement. Meanwhile, the hybrid reinforcement only increased the impact energy of the composite by 2.60% at 2 wt% Fe-SnS addition, beyond which the impact strength decreased. A marginal decrease in the weight of the composite with an increase in hybrid reinforcement was also observed. Hence, Fe-SnS hybrid particulates offered a favorable influence on the mechanical property performance of Al/Fe-SnS hybrid composites compared to that of the unreinforced Al matrix.